The power of possibility in landscape governance: Multiple lives of participatory action research in Kajang, Sulawesi - Fisher, M.; Mulyana, A.; Labarani, A.; Kamaluddin; Yuliani, E.L.; Moeliono, M. (Routledge, 2023)
In 2016, Indigenous communities began to gain access to land rights in Indonesia’s vast state forests. The Kajang community of Sulawesi was the first to achieve such legal land status. Kajang also gained attention for its use of PAR to gain consensus across stakeholder groups in securing recognition. The jointly produced local regulation became symbolic for its ability to convene activists and local government, with Kajang Indigenous leaders at the center. This chapter revisits this process and describes two subsequent PAR initiatives aiming to support landscape governance and empower Kajang institutions. The research teams were directly involved in facilitating PAR processes. This team generated data through reflective discussions with each of the main stakeholder groups. Findings show that PAR continued to resonate beyond formal regulatory initiatives, translating into opportunities for pursuing sustainable landscapes. Also critically explored are contradictions and unintended consequences of normative approaches, especially implications for marginalized groups with limited access to land. The chapter thus points to design elements that change over the course of PAR and suggests some grounding principles for charting a course toward sustainable landscapes. Across PAR’s multiple lives described here, stakeholders continue to engage with PAR for its power of possibility.